Síntese e caracterização de óxidos semicondutores com atividade fotocatalítica ampliada, para aplicação em fotocatálise heterogênea solar - França, Marcela Dias (2015)
In the present work, synthesis routes were studied in order to obtain TiO2-based catalysts with high photocatalytic activity. The variables synthesis evaluated were: titanium tetraisopropoxide / 2-propanol molar ratio, hydrolysis temperature, stirring time after hydrolysis, heat treatment and stirring type. The 16 synthesized catalysts called M01 to M16 were obtained using fractional factorial design 25-1. The results of photodegradation reactions showed to be satisfactory, leading to 89; 98 and 100% discoloration and 33; 49 and 62% mineralization of P4R dye. P25 catalyst led to 100% discoloration and 83% mineralization. XRD results showed the catalysts presented high crystallinity and crystallite size estimated at 14.90; 15.90 and 6.58 nm for M02, M03 and M10. Furthermore XRD showed the predominance of anatase phase in all catalysts while the brookite phase was detected only in catalysts submitted to hydrothermal treatment. Values found for BET surface area were 48.99; 54.80 and 176.60 m2/g, and catalysts submitted to hydrothermal heat treatment showed the largest surface areas. Moreover, a study in order to increase the efficiency of the M10 was carried out evaluating stirring time and heat treatment time variables separately. The stirring time was raised to 24 hours and hydrothermal reaction time was evaluated in 2; 4; 8; 12 and 16 hours leading to 45; 62; 75; 66 e 60% mineralization, respectively. A composite was then synthesized by associating M20 catalyst with zinc phthalocyanine photosensitizer dye obtaining the composite M20/ZnPc 1.6% m/m. The resulted compound presented a considerable improvement in efficiency by using sunlight as the radiation source. M20 / FtZn 1.6% m/m composite obtained 75.71% mineralization against 68% using M20 pure catalyst. By the use of dye association with M20 was observed a larger effect in discoloration. Results showed 79% discoloration for M19 catalyst whereas M20/FtZn 1.6% m/m obtained 96% discoloration, both from accumulated irradiation dose of 300 kJ/m2.